2005
DOI: 10.1002/art.21358
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind, randomized, controlled clinical trial of clofazimine compared with chloroquine in patients with systemic lupus erythematosus

Abstract: Objective. To evaluate the efficacy of clofazimine (CFZ) compared with chloroquine diphosphate (CDP) for the treatment of cutaneous involvement in systemic lupus erythematosus (SLE).Methods. A prospective, randomized, controlled, double-blind clinical trial was carried out in SLE patients with active cutaneous lesions, of whom 16 were randomized to receive CFZ at 100 mg/day and 17 received CDP at 250 mg/day for 6 months. All drugs had a similar appearance to avoid identification. Both groups received broad-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 24 publications
1
51
0
4
Order By: Relevance
“…This discoloration is evident within weeks of beginning treatment, fades months to years after the cessation of treatment, and occurs in a significant percentage of patients (16,33,42). CFM-induced skin discoloration has also been observed during treatment of M. avium complex and MDR TB infections, as well as during clinical trials to investigate the usefulness of CFM in inflammatory diseases, suggesting that this phenomenon is not leprosy specific (9,16,24,43). The reports available suggest that the intensity, duration, and prevalence of skin discoloration are dependent on the dose and duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This discoloration is evident within weeks of beginning treatment, fades months to years after the cessation of treatment, and occurs in a significant percentage of patients (16,33,42). CFM-induced skin discoloration has also been observed during treatment of M. avium complex and MDR TB infections, as well as during clinical trials to investigate the usefulness of CFM in inflammatory diseases, suggesting that this phenomenon is not leprosy specific (9,16,24,43). The reports available suggest that the intensity, duration, and prevalence of skin discoloration are dependent on the dose and duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of its bioaccumulation, several clinical trials have established CFZ as a potentially useful therapeutic agent for treating a variety of chronic inflammatory diseases (17)(18)(19)(20)(21)(22). Furthermore, in vitro studies have shown that intracellular CFZ biocrystals dampen proinflammatory pathways while enhancing anti-inflammatory signals (23).…”
mentioning
confidence: 99%
“…[77][78][79][80] In 2005, a randomized, double-blind, controlled trial compared clofazimine (100 mg per day) with chloroquine (250 mg per day) in 33 patients with SLE and active skin lesions (ACLE, SCLE, localized and disseminated DLE). 81 At the end of the 6-month study, a complete response was seen in 18.8% of patients treated with clofazimine as compared with 41.2% of patients treated with chloroquine, but the difference was not significant. A good response was observed in 12 of 16 patients (75%) from the clofazimine group and in 14 of 17 patients (82.4%) from the chloroquine group.…”
Section: Clofaziminementioning
confidence: 78%